Method for recovering copper by electrolysis from PCB hydrogen peroxide micro-etching waste liquid after heating and breaking up
Patent Information
- Application Number
- CN202611003225.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]有鉴于此,本发明的目的在于提出一种PCB双氧水微蚀废液加热破析电解回收铜的方法,以解决现有技术中二次污染严重、废气外溢以及资源浪费的问题
本发明通过催化剂预处理与多级热破解的协同作用,显著破坏废液中双氧水稳定剂及有机络合物,使铜离子充分释放,与直接加热或单一化学还原相比,铜离子释放率提高20%以上,为后续电解回收创造良好条件,有效解决了传统工艺中铜回收率低、残液含铜量高的问题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment, and in particular to a method for recovering copper by heating, breaking down, and electrolyzing PCB hydrogen peroxide micro-etching waste liquid. Background Technology
[0002] The micro-etching process in PCB (Printed Circuit Board) production is a key process in circuit forming and surface treatment. This process usually uses a mixture of high-concentration hydrogen peroxide and sulfuric acid to roughen the copper surface through micro-etching, in order to enhance the adhesion and bonding strength of subsequent processes. Due to long-term production operation, copper ions and impurities gradually accumulate in the micro-etching bath, resulting in a decline in process efficiency. Therefore, it is necessary to regularly discharge and replenish fresh micro-etching solution, thereby continuously producing a large amount of hydrogen peroxide micro-etching waste liquid.
[0003] In existing technologies, the traditional treatment of high-concentration hydrogen peroxide waste liquid mainly involves chemical digestion by adding reducing agents such as sodium thiosulfate or sodium sulfite. This method increases treatment costs due to the large amount of reagents consumed, and also introduces a large amount of sodium salt, leading to the accumulation of secondary pollutants and increasing the load on subsequent biochemical treatment. In addition, traditional processes promote the thermal decomposition of hydrogen peroxide through simple heating, but due to the lack of precise temperature control and system process design, the hydrogen peroxide is not completely decomposed, and the acidic waste gas generated during the heating process overflows, causing air pollution, low thermal energy utilization, and serious energy waste.
[0004] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop a method for recovering copper by heating, breaking down, and electrolyzing PCB hydrogen peroxide micro-etching waste liquid. Summary of the Invention
[0005] In view of this, the purpose of this invention is to propose a method for recovering copper by heating, breaking down, and electrolyzing PCB hydrogen peroxide micro-etching waste liquid, so as to solve the problems of serious secondary pollution, waste gas overflow, and resource waste in the prior art.
[0006] To achieve the above objectives, the present invention provides a method for recovering copper by heating, breaking down, and electrolyzing PCB hydrogen peroxide micro-etching waste liquid.
[0007] A method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid through heating, decomposition, and electrolysis, wherein the specific preparation steps of the method are as follows: Step S1: Add hydrogen peroxide micro-etching waste liquid to the catalyst bed, heat to 20-30℃, introduce mixed gas, pressurize to 0.03-0.05MPa, and maintain a total gas space velocity of 500-1000h. -1 The reaction is completed after 40-60 minutes, yielding a pretreated solution. Step S2: Add the pretreatment liquid to the multi-stage thermal decomposition reaction module, raise the temperature step by step at a rate of 3-5℃ / min, treat 300-500L / h of waste liquid, perform three-stage condensation and recovery, and treat for 3-4 hours. After treatment, pyrolysis liquid and non-condensable oxygen-enriched gas are obtained respectively. Step S3: Add the pyrolysis solution to the three-stage reaction tank, with a cathode potential of -0.15-0.25V and a cathode current density of 10-30A / m. 2 With an electrode spacing of 30-50mm and a rotation speed of 60-80rpm, non-condensable oxygen-enriched gas is introduced, with an aeration intensity of 0.1-0.3vvm and a treatment time of 40-60min / batch. After treatment, the temperature is controlled to 93-97℃ by PID, the rotation speed is 80-100rpm, and the reaction is kept at the temperature for 70-90min. The hydrogen peroxide concentration is adjusted to 1-2g / L to obtain a mixed solution. Step S4: Add the mixture to the diaphragm electrolytic cell, heat the cathode chamber to 90-95℃, heat the anode chamber to 85-90℃, set the electrode spacing to 30-40mm, and the cathode current density to 100-200A / m. 2 With a voltage of 2.5-3.5V, 100-200g / L sulfuric acid is added to the anode chamber, and an asymmetric square wave pulsed current is applied at a current density of 200-400A / m. 2 The on-time was 30-50ms, the off-time was 10-30ms, the frequency was 30-50Hz, and the deposition time was 6-8h, yielding deposited copper, oxygen, and hydrogen.
[0008] When the system is first started, hydrogen and non-condensable oxygen-enriched gas are supplied by the stored gas source. After steps S2 and S4 are running stably and producing by-product hydrogen and non-condensable oxygen-enriched tail gas, the system is gradually switched to the gas source provided by steps S2 and S4 to achieve closed-loop gas circulation.
[0009] In step S3, the adjustment of hydrogen peroxide concentration does not rely on the addition of any chemical reagents, but is achieved entirely through the control of physical process parameters. Specifically, the waste liquid in the three-stage reaction tank is precisely maintained in the high-efficiency decomposition temperature range of 93-97℃ by a PID temperature control system, and the stirring speed is set to 80-100 rpm to ensure uniform heat transfer. Under these conditions, hydrogen peroxide continues to decompose. In addition, an automatic sampling and titration device is installed in the tank to obtain the hydrogen peroxide concentration value in real time. When the concentration is close to the target upper limit of 2 g / L, the current parameters are maintained. When the concentration decreases too slowly or deviates from the target range, the control system appropriately extends the heat preservation time until the hydrogen peroxide concentration stabilizes in the range of 1-2 g / L.
[0010] Preferably, the mixed gas in step S1 includes hydrogen, nitrogen and non-condensable oxygen-enriched gas, the non-condensable oxygen-enriched gas comes from step S2 in the continuous production process, the hydrogen comes from the hydrogen evolved in the cathode chamber in step S4 in the continuous production process, and the hydrogen volume concentration is ≤4%.
[0011] Preferably, the catalyst preparation steps in step S1 are as follows: Step A1: Add spherical activated carbon to deionized water, heat to 90-100℃, wash for 30-40 min, remove and drain, add 5wt% nitric acid solution, heat to 50-60℃, treat for 4-5 h, after treatment is complete, wash with deionized water, adjust pH to 6.8-7.2, dry, then place in a muffle furnace, introduce nitrogen gas, heat to 340-360℃, calcine for 3-4 h, after calcine is complete, cool to 20-30℃ to obtain the pretreated carrier; Step A2: Add chloroplatinic acid and palladium chloride to deionized water, stir at 100-200 rpm for 15-25 minutes, add isopropanol as dispersant, stir for 8-12 minutes, and after stirring is complete, the impregnation solution is obtained; Step A3: Add the pretreated support to the impregnation flask, reduce the pressure to -0.08 to -0.09 MPa, degas for 30-40 min, add the impregnation solution, impregnate for 2-3 h, after impregnation is complete, restore to normal pressure, and rotary evaporate to obtain the catalyst precursor; Step A4: Under a hydrogen and nitrogen atmosphere, add the catalyst precursor into a tube furnace, heat to 260-300℃ at a heating rate of 3-5℃ / min, and carry out the reduction reaction for 4-6 hours. After the reaction is complete, cool down to 20-30℃ and purge with nitrogen for 30-40 minutes to obtain the catalyst.
[0012] Preferably, the mass ratio of chloroplatinic acid, palladium chloride, dispersant, and deionized water in step A2 is 0.052-0.056:0.015-0.019:0.054-0.058:1; The mass ratio of the pretreated carrier to the impregnation solution in step A3 is 1:0.5-0.9; In step A4, the volume ratio of hydrogen to nitrogen is 0.15-0.2:1.
[0013] Preferably, the multi-stage thermal cracking reaction module in step S2 includes a preheating tank, a primary cracking tank, a secondary reaction stirring tank, and a tertiary reaction tank; The stepwise heating in step S2 is as follows: preheating tank temperature 40-60℃, first-stage reaction tank temperature 86-90℃, second-stage reaction stirring tank temperature 88-90℃, and third-stage reaction tank temperature 93-97℃.
[0014] Preferably, the three-stage condensation recovery in step S2 is as follows: the first stage cools down to 80-90°C, recovers the acidic condensate and returns it to the first-stage cracking tank to replenish the acidity consumed in the cracking process and promote the decomposition of hydrogen peroxide; the second stage cools down to 40-50°C, recovers the oxygen-containing condensate, and uses it as makeup water for the electrolytic anode in step S4; and the third stage yields non-condensable oxygen-rich gas.
[0015] Preferably, a portion of the non-condensable oxygen-enriched gas is returned to step S1 to be mixed with hydrogen, while the other portion is introduced into the preheating tank and the bottom of the primary breaking tank for microbubble aeration, with an aeration intensity of 0.2-0.5 vvm.
[0016] Preferably, the three-stage reaction tank in step S3 is equipped with a liftable electrode assembly, wherein the cathode of the liftable electrode assembly is made of stainless steel plate and the anode is a titanium-based iridium-tantalum coated DSA anode.
[0017] Preferably, the diaphragm in the diaphragm electrolyzer in step S4 is a perfluorosulfonic acid type cation exchange membrane with a thickness of 0.15-0.20 mm.
[0018] Preferably, the cathode chamber in step S4 is equipped with an online hydrogen detector. When the hydrogen concentration is ≥1%, an alarm is triggered and the exhaust is increased; when it is ≥2%, the hydrogen delivery valve is closed and the chamber is purged with nitrogen; and when it is ≥4%, the electrolysis power supply is cut off. The oxygen released from the anode chamber in step S4 is collected and dried by acid mist, and then combined with the third-stage non-condensable oxygen-enriched gas in step S2.
[0019] The beneficial effects of this invention are: This invention significantly destroys hydrogen peroxide stabilizers and organic complexes in waste liquid through the synergistic effect of catalyst pretreatment and multi-stage thermal decomposition, allowing copper ions to be fully released. Compared with direct heating or single chemical reduction, the copper ion release rate is increased by more than 20%, creating favorable conditions for subsequent electrolytic recovery and effectively solving the problems of low copper recovery rate and high copper content in residual liquid in traditional processes.
[0020] This invention employs a three-stage condensation and recycling technology, which returns the acidic condensate generated by thermal decomposition to the decomposition tank to maintain acidity, uses oxygen-containing condensate for electrolytic anode makeup water, and returns non-condensable oxygen-enriched gas to the system for catalytic hydrogenation and aeration. This achieves full-component resource utilization of waste liquid, waste gas, and condensate, significantly reducing pollutant discharge and avoiding secondary pollution.
[0021] This invention employs an asymmetric square-wave pulsed current in conjunction with a diaphragm electrolytic cell during the electrolysis stage, effectively reducing the thickness of the cathode diffusion layer, suppressing dendrite growth, and obtaining dense and smooth deposited copper. Simultaneously, online hydrogen detection in the cathode chamber and a multi-level safety interlock mechanism ensure that the hydrogen concentration remains below the lower explosive limit, significantly improving process safety.
[0022] This invention utilizes non-condensable oxygen-enriched gas and hydrogen produced during the thermal decomposition process for internal system circulation, significantly reducing the cost of purchased gases. At the same time, the oxygen evolved in the electrolytic anode chamber is captured, dried, and then combined with the non-condensable oxygen-enriched gas, further improving oxygen utilization.
[0023] This invention integrates multiple units such as catalytic pretreatment, multi-stage thermal cracking, condensation fractionation, pulse electrolysis, and gas recycling to form a closed-loop process flow. The entire method has a high degree of automation, can operate continuously and stably, and has a flexible and adjustable processing scale. It is suitable for online or offline resource recovery treatment of micro-etching waste liquid in PCB manufacturing enterprises and has broad application prospects. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0025] Example 1: Preparation of a catalyst: S1: Add 1000g of spherical activated carbon to 2000mL of deionized water, heat to 90℃, wash for 40min, remove and drain, add 1500mL of 5wt% nitric acid solution, heat to 50℃, treat for 5h, after treatment is complete, wash with deionized water, adjust pH to 6.8-7.2, dry, then place in a muffle furnace, introduce nitrogen gas, heat to 340℃, calcine for 4h, after calcine is complete, cool to 20℃ to obtain the pretreated carrier; S2: Add 52g of chloroplatinic acid and 15g of palladium chloride to 1000g of deionized water, stir at 100rpm for 25min, add 54g of dispersant isopropanol, stir for 8min, and the stirring is complete to obtain the impregnation solution. S3: Add 100g of pretreated carrier to an impregnation flask, degas under reduced pressure of -0.08MPa for 40min, add 50g of impregnation liquid, impregnate for 2h, after impregnation is complete, restore to normal pressure, and rotary evaporate to obtain catalyst precursor; S4: Under a hydrogen and nitrogen atmosphere, 100g of catalyst precursor was added to a tube furnace, heated to 260℃ at a heating rate of 5℃ / min, and the reduction reaction was carried out for 4 hours. After the reaction was completed, the temperature was lowered to 30℃ and nitrogen was purged for 30 minutes to obtain the catalyst.
[0026] Example 2: Preparation of a catalyst: S1: Add 1000g of spherical activated carbon to 2000mL of deionized water, heat to 95℃, wash for 35min, remove and drain, add 1500mL of 5wt% nitric acid solution, heat to 55℃, treat for 4.5h, after treatment is complete, wash with deionized water, adjust pH to 6.8-7.2, dry, then place in a muffle furnace, introduce nitrogen gas, heat to 350℃, calcine for 3.5h, after calcine is complete, cool to 25℃ to obtain the pretreated carrier; S2: Add 54g of chloroplatinic acid and 17g of palladium chloride to deionized water, stir at 150rpm for 20min, add 56g of dispersant isopropanol, stir for 10min, and the impregnation solution is obtained after stirring is completed. S3: Add 100g of pretreated carrier to an impregnation flask, degas under reduced pressure (-0.085MPa) for 35min, add 70g of impregnation liquid, impregnate for 2.5h, after impregnation is complete, restore to normal pressure, and rotary evaporate to obtain catalyst precursor; S4: Under a hydrogen and nitrogen atmosphere, 100g of catalyst precursor was added to a tube furnace, heated to 280℃ at a heating rate of 4℃ / min, and the reduction reaction was carried out for 5h. After the reaction was completed, the temperature was lowered to 25℃ and nitrogen was purged for 35min to obtain the catalyst.
[0027] Example 3: Preparation of a catalyst: S1: Add 1000g of spherical activated carbon to 2000mL of deionized water, heat to 100℃, wash for 30min, remove and drain, add 1500mL of 5wt% nitric acid solution, heat to 60℃, treat for 4h, after treatment is complete, wash with deionized water, adjust pH to 6.8-7.2, dry, then place in a muffle furnace, introduce nitrogen gas, heat to 360℃, calcine for 3h, after calcine is complete, cool to 30℃ to obtain the pretreated carrier; S2: Add 56g of chloroplatinic acid and 19g of palladium chloride to 1000g of deionized water, stir at 200rpm for 15min, add 58g of dispersant isopropanol, stir for 12min, and the impregnation solution is obtained after stirring is completed. S3: Add 100g of pretreated carrier to an impregnation flask, degas under reduced pressure of -0.09MPa for 40min, add 90g of impregnation liquid, impregnate for 2h, after impregnation is complete, restore to normal pressure, and rotary evaporate to obtain catalyst precursor; S4: Under a hydrogen and nitrogen atmosphere, 100g of catalyst precursor was added to a tube furnace, heated to 300℃ at a heating rate of 3℃ / min, and the reduction reaction was carried out for 6 hours. After the reaction was completed, the temperature was lowered to 20℃ and nitrogen was purged for 40 minutes to obtain the catalyst.
[0028] Example 4: A method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid through heating, decomposition, and electrolysis. S1: Add hydrogen peroxide micro-etching waste liquid to the catalyst bed (Example 1), heat to 20°C, introduce mixed gas, pressurize to 0.05 MPa, and set the total gas space velocity to 500 h⁻¹. -1 The reaction was completed after 60 minutes, yielding a pretreated solution. S2: Add the pretreatment liquid to the preheating tank, heat it to 40℃, and let it flow into the first-stage cracking tank. Heat it to 90℃, let it flow into the second-stage reaction stirring tank, heat it to 88℃, and let it flow into the third-stage reaction tank. Heat it to 97℃, with a heating rate of 3℃ / min and a waste liquid treatment capacity of 500L / h. Recover the condensed gas in the third stage. In the first stage, cool it down to 80℃ and recover the acidic condensate, which is then returned to the first-stage cracking tank. In the second stage, cool it down to 50℃ and recover the oxygen-containing condensate. In the third stage, non-condensable oxygen-enriched gas is obtained. The treatment time is 3 hours. After the treatment is completed, pyrolysis liquid and non-condensable oxygen-enriched gas are obtained respectively. S3: Add the pyrolysis solution to the three-stage reaction tank, which is equipped with a liftable electrode assembly. The cathode of the liftable electrode assembly is made of stainless steel plate, and the anode is a titanium-based iridium-tantalum coated DSA anode. The cathode potential is -0.15V, and the cathode current density is 30A / m. 2 With an electrode spacing of 30 mm and a rotation speed of 80 rpm, non-condensable oxygen-enriched gas was introduced, with an aeration intensity of 0.1 vvm and a treatment time of 60 min / batch. After treatment, the temperature was controlled to 93℃ by PID, the rotation speed was 100 rpm, and the reaction was kept at the temperature for 70 min. The hydrogen peroxide concentration was adjusted to 2 g / L to obtain a mixed solution. S4: Add the mixture to the diaphragm electrolytic cell. The diaphragm in the diaphragm electrolytic cell is a perfluorosulfonic acid type cation exchange membrane with a thickness of 0.15 mm. The cathode chamber is heated to 90°C, the anode chamber is heated to 90°C, the electrode spacing is 30 mm, and the cathode current density is 200 A / m. 2 The voltage is 2.5V. 200g / L sulfuric acid is added to the anode chamber. An online hydrogen detector and hydrogen collection pipe are installed in the cathode chamber. Hydrogen gas evolved in the cathode chamber is condensed, demisted, and dried before being combined with the mixed gas from step S1 for hydrogenation reaction in the catalyst bed. To ensure safety, the hydrogen volume concentration after combination is controlled at ≤4%. An alarm is triggered and exhaust is increased when the hydrogen concentration is ≥1%. When it is ≥2%, the hydrogen delivery valve is closed and nitrogen is used for purging. When it is ≥4%, the electrolysis power supply is cut off. Oxygen gas evolved in the anode chamber is collected and dried by acid mist, then combined with the non-condensable oxygen-enriched gas from the third stage of step S2 and returned to the system for catalytic hydrogenation in step S1 and aeration in step S3. An asymmetric square wave pulse current with a current density of 400A / m² is applied. 2 With a conduction period of 30ms, a turn-off period of 10ms, a frequency of 50Hz, and a deposition time of 6h, deposited copper was obtained.
[0029] Example 5: A method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid through heating, decomposition, and electrolysis. S1: Add hydrogen peroxide micro-etching waste liquid to the catalyst bed (Example 2), heat to 25°C, introduce mixed gas, pressurize to 0.04 MPa, and set the total gas space velocity to 850 h⁻¹. -1 The reaction was completed after 50 minutes, yielding a pretreated solution. S2: Add the pretreatment liquid to the preheating tank, heat it to 50℃, and let it flow into the first-stage cracking tank. Heat it to 88℃, let it flow into the second-stage reaction stirring tank, heat it to 89℃, and let it flow into the third-stage reaction tank. Heat it to 95℃, with a heating rate of 4℃ / min and a waste liquid treatment capacity of 400L / h. Recover the condensed gas in the third stage. In the first stage, cool it down to 85℃ and recover the acidic condensate, which is then returned to the first-stage cracking tank. In the second stage, cool it down to 45℃ and recover the oxygen-containing condensate. In the third stage, obtain non-condensable oxygen-enriched gas. The treatment time is 3.5h. After the treatment is completed, pyrolysis liquid and non-condensable oxygen-enriched gas are obtained respectively. S3: Add the pyrolysis solution to the three-stage reaction tank, which is equipped with a liftable electrode assembly. The cathode of the liftable electrode assembly is made of stainless steel plate, and the anode is a titanium-based iridium-tantalum coated DSA anode. The cathode potential is -0.2V, and the cathode current density is 20A / m. 2 With an electrode spacing of 40 mm and a rotation speed of 70 rpm, non-condensable oxygen-enriched gas was introduced, with an aeration intensity of 0.2 vvm and a treatment time of 50 min / batch. After treatment, the temperature was controlled to 95℃ by PID, the rotation speed was 90 rpm, and the reaction was kept at the temperature for 80 min. The hydrogen peroxide concentration was adjusted to 1.5 g / L to obtain a mixed solution. S4: Add the mixture to the diaphragm electrolytic cell. The diaphragm in the diaphragm electrolytic cell is a perfluorosulfonic acid type cation exchange membrane with a thickness of 0.18 mm. The cathode chamber is heated to 93°C, the anode chamber is heated to 87°C, the electrode spacing is 35 mm, and the cathode current density is 150 A / m. 2 The voltage is 3V. Sulfuric acid of 150g / L is added to the anode chamber. An online hydrogen detector and hydrogen collection pipe are installed in the cathode chamber. Hydrogen gas evolved in the cathode chamber is condensed, demisted, and dried before being combined with the mixed gas from step S1 for hydrogenation reaction in the catalyst bed. To ensure safety, the hydrogen volume concentration after combination is controlled at ≤4%. An alarm is triggered and exhaust is increased when the hydrogen concentration is ≥1%. At ≥2%, the hydrogen delivery valve is closed and nitrogen is used for purging. At ≥4%, the electrolysis power supply is cut off. Oxygen gas evolved in the anode chamber is collected and dried by acid mist capture before being combined with the non-condensable oxygen-enriched gas from the third stage of step S2. Both are returned to the system for catalytic hydrogenation in step S1 and aeration in step S3. An asymmetric square wave pulse current with a current density of 300A / m² is applied. 2 With a conduction period of 40ms, a turn-off period of 20ms, a frequency of 40Hz, and a deposition time of 7h, deposited copper was obtained.
[0030] Example 6: A method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid through heating, decomposition, and electrolysis. S1: Add hydrogen peroxide micro-etching waste liquid to the catalyst bed (Example 3), heat to 30°C, introduce mixed gas, pressurize to 0.03 MPa, and set the total gas space velocity to 1000 h⁻¹. -1 The reaction was completed after 40 minutes, yielding a pretreated solution. S2: Add the pretreatment liquid to the preheating tank, heat it to 60℃, and let it flow into the first-stage cracking tank. Heat it to 86℃, let it flow into the second-stage reaction stirring tank, heat it to 90℃, and let it flow into the third-stage reaction tank. Heat it to 93℃, with a heating rate of 5℃ / min and a waste liquid treatment capacity of 300L / h. Recover the condensed gas in the third stage. In the first stage, cool it down to 90℃ and recover the acidic condensate, which is then returned to the first-stage cracking tank. In the second stage, cool it down to 40℃ and recover the oxygen-containing condensate. In the third stage, non-condensable oxygen-enriched gas is obtained. The treatment time is 4 hours. After the treatment is completed, pyrolysis liquid and non-condensable oxygen-enriched gas are obtained respectively. S3: Add the pyrolysis solution to the three-stage reaction tank, which is equipped with a liftable electrode assembly. The cathode of the liftable electrode assembly is made of stainless steel plate, and the anode is a titanium-based iridium-tantalum coated DSA anode. The cathode potential is -0.25V, and the cathode current density is 10A / m. 2 With an electrode spacing of 50 mm and a rotation speed of 60 rpm, non-condensable oxygen-enriched gas was introduced, with an aeration intensity of 0.1 vvm and a treatment time of 60 min / batch. After treatment, the temperature was controlled to 93℃ by PID, the rotation speed was 100 rpm, and the reaction was kept at the temperature for 70 min. The hydrogen peroxide concentration was adjusted to 2 g / L to obtain a mixed solution. S4: Add the mixture to the diaphragm electrolytic cell. The diaphragm in the diaphragm electrolytic cell is a perfluorosulfonic acid type cation exchange membrane with a thickness of 0.20 mm. The cathode chamber is heated to 95°C, the anode chamber is heated to 85°C, the electrode spacing is 40 mm, and the cathode current density is 100 A / m. 2 The voltage is 3.5V. 100g / L sulfuric acid is added to the anode chamber. An online hydrogen detector and hydrogen collection pipe are installed in the cathode chamber. The hydrogen gas evolved in the cathode chamber is condensed, demisted, and dried before being combined with the mixed gas from step S1 for hydrogenation reaction in the catalyst bed. To ensure safety, the hydrogen volume concentration after combination is controlled at ≤4%. An alarm is triggered and exhaust is increased when the hydrogen concentration is ≥1%, closed when it is ≥2%, and purged with nitrogen when it is ≥4%, and the electrolysis power supply is cut off when it is ≥4%. The oxygen gas evolved in the anode chamber is collected and dried by acid mist, then combined with the non-condensable oxygen-enriched gas from the third stage of step S2 and returned to the system for catalytic hydrogenation in step S1 and aeration in step S3. An asymmetric square wave pulse current with a current density of 400A / m² is applied. 2 With a conduction period of 30ms, a turn-off period of 30ms, a frequency of 30Hz, and a deposition time of 8h, deposited copper was obtained.
[0031] Comparative Example 1: The difference between this comparative example and Example 4 is that: no catalyst bed is added in step S1, the hydrogen peroxide micro-etching waste liquid is directly heated to 20°C, mixed gas is introduced, pressurized to 0.05MPa, and reacted for 40 minutes. The remaining steps and parameters are the same as in Example 4, and finally deposited copper is obtained.
[0032] Comparative Example 2: The difference between this comparative example and Example 4 is that: in step S2, the preheating tank and multi-stage cracking tank are not used. Instead, the pretreatment liquid is directly added to a separate heating vessel, heated to 93°C in one go, and kept at that temperature for 3 hours. There is no stepwise heating and three-stage condensation recovery. The remaining steps and parameters are the same as in Example 4, and finally, deposited copper is obtained.
[0033] Comparative Example 3: The difference between this comparative example and Example 4 is that the gas generated by thermal cracking in step S2 is not recycled through three-stage condensation, but is directly discharged into the atmosphere; the acidic condensate is not recycled back to the cracking tank, nor are the oxygen-containing condensate and non-condensable oxygen-enriched gas recycled; the hydrogen and nitrogen in the mixed gas in step S1 come from an external gas source, and the non-condensable oxygen-enriched gas in the system is not used. The remaining steps and parameters are the same as in Example 4, and finally, deposited copper is obtained.
[0034] Comparative Example 4: Compared with Example 4, the difference in this comparative example is that the asymmetric square wave pulse current is removed in step S4 and replaced with conventional DC electrolysis. The parameters such as current density, voltage, and temperature remain unchanged, while the remaining steps and parameters are the same as in Example 4, and finally deposited copper is obtained.
[0035] Comparative Example 5: Compared with Example 4, the difference in this comparative example is that in step S3, cathode potential control is not performed, non-condensable oxygen-enriched gas aeration is not performed, the waste liquid is simply stirred in the three-stage reaction tank and the temperature is controlled to 93°C by PID. After the reaction is kept at the temperature, the hydrogen peroxide concentration is adjusted. The remaining steps and parameters are the same as in Example 4, and finally deposited copper is obtained.
[0036] Performance testing: Copper recovery rate test: The Agilent-5110 inductively coupled plasma atomic emission spectrometer was used in accordance with the HJ 776-2015 testing standard. Take the PCB hydrogen peroxide micro-etching waste liquid (Cu) 2+ Add 1 mL of 30 g / L to a 100 mL volumetric flask, add 5 mL of pure nitric acid, dilute to the mark with deionized water, shake well, let stand for 30 min, filter, and set aside. Take 50 mL of the residual liquid after electrolysis from Examples 4-6 and Comparative Examples 1-5 respectively, add 5 mL of pure nitric acid, heat to 120°C, digest to about 5 mL, cool and add to a 100 mL volumetric flask, dilute to the mark with deionized water, shake well, filter and set aside. Blank group: Deionized water was used instead of the sample, and the same digestion and volume adjustment steps were performed as a blank control. Preparation of standard solution: Take 1.0 g of pure copper, dissolve it in 20 mL of 68% nitric acid, add deionized water to make up to 1 L, and obtain standard solution; Preparation of standard series: Take the standard solution, dilute it with 2% nitric acid solution, and prepare concentrations of 0.10, 0.50, 1.00, 5.00, 10.00, and 20.00 mg / L; ICP-OES instrument operating conditions: RF power 1.2kW, plasma gas flow rate 12.0L / min, auxiliary gas flow rate 1.0L / min, nebulizing gas flow rate 0.7L / min; Copper recovery rate calculation:
[0037] in: R: Copper recovery rate, % C0: Mass concentration of copper ions in PCB hydrogen peroxide micro-etching waste liquid, g / L; V0: Volume of hydrogen peroxide micro-etching waste liquid for PCB, in L; C1: Mass concentration of copper ions in the residual liquid after electrolysis, g / L; V1: Volume of residual liquid after electrolysis, in L; Deposited copper purity test: Referencing the GB / T 5121.1-2008 testing standard, an electronic balance was used. Take 1.0 g of the deposited copper from Examples 4-6 and Comparative Examples 1-5 respectively, wash 3 times with deionized water and 2 times with anhydrous ethanol, heat to 105°C, dry for 30 min, cool and weigh, and record M. s Add 20 mL of nitric acid-sulfuric acid mixture, heat until white fumes appear, cool, add 50 mL of deionized water to rinse the watch glass and cup walls, heat again to a gentle boil to dissolve the salts, cool to room temperature to obtain the solution; The platinum cathode was washed, dried, and weighed, and M1 was recorded. The solution was added to deionized water and diluted to 100 mL. Electrolysis was then performed with a cathode current density of 2 A / dm³. 2 At a temperature of 40-50℃ and a rotation speed of 300rpm, electrolyze until the electrolyte is colorless or very pale blue. After electrolysis, turn off the stirring and heating, remove the cathode, wash and dry it. After drying, cool and weigh it, and record it as M2. Calculation of the mass fraction of copper in deposited copper:
[0038] Table 1 Test Results of Examples and Comparative Examples Example 4 0.35 98.83 0.9985 99.85 Example 5 0.38 98.73 0.9982 99.82 Example 6 0.32 98.93 0.9988 99.88 Comparative Example 1 6.20 79.33 0.9520 95.20 Comparative Example 2 5.80 80.67 0.9640 96.40 Comparative Example 3 4.50 85.00 0.9680 96.80 Comparative Example 4 2.10 93.00 0.9420 94.20 Comparative Example 5 3.50 88.33 0.9750 97.50 Hydrogen peroxide decomposition rate test Referencing the GB / T 1616-2014 testing standard, a 25mL acid burette was used. Test principle:
[0039] Take 10 mL of PCB hydrogen peroxide micro-etching waste liquid, add 20 mL of 2 mol / L sulfuric acid solution, shake well, and add 0.1 mol / L potassium permanganate solution dropwise until the solution just turns slightly red and does not fade within 30 seconds. Record the volume V of potassium permanganate standard solution consumed. 原 (Unit: mL); Take 10 mL of the mixture from Examples 4-6 and Comparative Examples 1-5 before adjustment in step S3, repeat the above steps, and record the volume V of potassium permanganate standard solution consumed. 混合 (Unit: mL), and a blank control group was also set up; Hydrogen peroxide concentration calculation:
[0040] V(V) 原 / V 混合 (Volume of potassium permanganate standard solution consumed in sample titration, mL) V0: Volume of potassium permanganate standard solution consumed in the titration, mL; C: Concentration of potassium permanganate standard solution, mol / L; M: Molar mass of H2O2, taken as 17.01 g / mol; V 样 Sample volume, mL; Calculation of hydrogen peroxide decomposition rate:
[0041] Table 2. Test results of hydrogen peroxide decomposition rate in the examples and comparative examples. Example 4 30.0 0.60 98.00 Example 5 30.0 0.68 97.73 Example 6 30.0 0.52 98.27 Comparative Example 1 30.0 8.50 71.67 Comparative Example 2 30.0 7.20 76.00 Comparative Example 3 30.0 5.50 81.67 Comparative Example 4 30.0 1.20 96.00 Comparative Example 5 30.0 1.00 96.67 Exhaust gas acid content test: The Dionex ICS-6000 ion chromatograph was used in accordance with the HJ 544-2016 testing standard. Sampling was performed at the outlet of the third-stage non-condensable oxygen-enriched gas in step S2 of Examples 4-6 and Comparative Examples 1-5, respectively. The absorption bottle contained 50 mL of 0.01 mol / L sodium hydroxide absorption solution, the sampling flow rate was 1.0 L / min, the sampling temperature was 25 °C, and the sampling time was 30 min. After sampling was completed, the vacuum pump was turned off, and the inner wall of the sampling tube was immediately rinsed with 5 mL of absorption solution. The solution was then combined with the solution in the absorption bottle, transferred to a 50 mL volumetric flask, and diluted to the mark. Then, 10 mL of the diluted absorption solution was added to the 50 mL volumetric flask and diluted to the mark to obtain the sample solution. Preparation of sulfate standard solution: Add 1000 mg / L SO4 2-The standard solutions were serially diluted with deionized water to prepare a series of standard solutions with concentrations of 0.5, 1.0, 2.0, 5.0, and 10.0 mg / L. Take 2 mL of sample solution and 2 mL of standard solution, filter through a 0.22 μm filter membrane, and perform ion chromatography analysis. Operating conditions: 20 mmol / L KOH eluent, 1.0 mL / min flow rate, 25 μL injection volume, AERS-500 suppressor, 50 mA current, 10 min run; calculate: Acid content test in exhaust gas: Refer to the HJ 544-2016 testing standard and use a Dionex ICS-6000 ion chromatograph; Sampling was performed at the outlet of the third-stage non-condensable oxygen-enriched gas in step S2 of Examples 4-6 and Comparative Examples 1-5, respectively. The absorption bottle contained 50 mL of 0.01 mol / L sodium hydroxide absorption solution, the sampling flow rate was 1.0 L / min, the sampling temperature was 25 °C, and the sampling time was 30 min. After sampling was completed, the vacuum pump was turned off, and the inner wall of the sampling tube was immediately rinsed with 5 mL of absorption solution. The solution was then combined with the solution in the absorption bottle, transferred to a 50 mL volumetric flask, and diluted to the mark. Then, 10 mL of the diluted absorption solution was added to the 50 mL volumetric flask and diluted to the mark to obtain the sample solution. Preparation of sulfate standard solution: Add 1000 mg / L SO4 2- The standard solutions were serially diluted with deionized water to prepare a series of standard solutions with concentrations of 0.5, 1.0, 2.0, 5.0, and 10.0 mg / L. Take 2 mL of sample solution and 2 mL of standard solution, filter through a 0.22 μm filter membrane, and perform ion chromatography analysis. Operating conditions: 20 mmol / L KOH eluent, 1.0 mL / min flow rate, 25 μL injection volume, AERS-500 suppressor, 50 mA current, 10 min run; calculate:
[0042] SO4 in the injected solution obtained from the standard curve 2- ⁻Mass concentration, mg / L; V 总 Final volume of absorbent solution, in L; D: Dilution factor; V 标 Sampling volume under standard conditions (0℃, 101.325kPa), m 3 V 采Actual sampling volume (L) = flow rate (L / min) × time (min); t: Temperature at the sampling point, °C; p: Atmospheric pressure at the sampling point, 101.3 kPa; Table 3. Test results of acid content in exhaust gas of the examples and comparative examples Example 4 0.05 15.0 Example 5 0.05 18.0 Example 6 0.05 12.0 Comparative Example 1 0.05 85.0 Comparative Example 2 0.05 120.0 Comparative Example 3 0.05 210.0 Comparative Example 4 0.05 20.0 Comparative Example 5 0.05 22.0 Data Analysis: As can be seen from Tables 1-3, the method for recovering copper by heating, decomposing and electrolyzing PCB hydrogen peroxide micro-etching waste liquid according to the present invention has a better copper recovery rate, higher purity of deposited copper, higher hydrogen peroxide decomposition rate and lower acid content in tail gas. In contrast, Comparative Example 1 did not have a catalyst bed in step S1, which resulted in the hydrogen peroxide stabilizer and organic complex not being effectively catalytically destroyed, and insufficient release of copper ions. This was because the platinum-palladium active sites on the catalyst surface were missing, which could not promote the hydrogenation reduction reaction between hydrogen and hydrogen peroxide stabilizer. At the same time, the hydrogen in the mixed gas was not catalytically activated and could not effectively combine with stabilizer molecules. In addition, the uncatalyzed waste liquid still contained a large amount of undestroyed stabilizer in the subsequent thermal decomposition process, which hindered the decomposition of hydrogen peroxide and the dissolution of copper ions. Comparative Example 2, due to the lack of a multi-stage thermal decomposition module, resulted in severe acidity loss and low thermal energy utilization during the hydrogen peroxide decomposition process. This was because rapid heating caused a large amount of volatile acid in the waste liquid to overflow with water vapor, making it impossible to maintain the system acidity through staged condensation and reflux. Hydrogen peroxide decomposes at a higher rate in an acidic environment, and the decrease in acidity directly inhibited the decomposition efficiency. At the same time, one-time high-temperature heating easily caused local overheating, which caused some organic matter to carbonize and encapsulate copper ions, hindering subsequent electrolysis. Comparative Example 3, lacking a three-stage condensation recovery system, failed to achieve resource recycling of acid, condensate, and non-condensable oxygen-enriched gas. This was because the first-stage acidic condensate could not be returned to replenish the acidity of the decomposition tank, resulting in insufficient acidity and a decreased decomposition rate in the later stages of hydrogen peroxide decomposition; the second-stage oxygen-containing condensate could not be used for anode makeup water, increasing fresh water consumption; and the third-stage non-condensable oxygen-enriched gas was directly discharged, resulting in the loss of oxygen that could be used for catalytic hydrogenation and aeration, and causing a large amount of acidic waste gas to be discharged. Furthermore, the hydrogen in step S1 needed to be replenished from an external gas source, increasing operating costs. Comparative Example 4, due to the lack of asymmetric square wave pulse current, resulted in a rough deposited copper layer, severe dendrite growth, and decreased purity. This was because the thickness of the diffusion layer on the cathode surface continuously increased under DC electrolysis, which limited the mass transfer of copper ions and easily led to the formation of dendritic crystals. These dendrites were loose and contained impurities, resulting in reduced purity. In contrast, the asymmetric square wave pulse current deposited rapidly during the conduction period and restored the diffusion layer during the off period, effectively weakening concentration polarization, inhibiting dendrite growth, and obtaining a dense and smooth deposited layer. In Comparative Example 5, the lack of cathode potential control and oxygen-enriched aeration in step S3 resulted in insufficient conversion of residual trace copper ions and reducing substances in the waste liquid. This is because cathode potential control can generate a weak reducing current, promoting the dissociation and pre-deposition of some complexed copper ions. At the same time, oxygen-enriched aeration can oxidize the residual reducing organic matter in the waste liquid, reducing its interference with subsequent membrane electrolysis. Without this step, some copper ions in the waste liquid still exist in a stable complexed state and cannot be effectively deposited during electrolysis.
[0043] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0044] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid through heating, decomposition, and electrolysis, characterized in that... The specific preparation steps of the method are as follows: Step S1: Add hydrogen peroxide micro-etching waste liquid to the catalyst bed, heat to 20-30℃, introduce mixed gas, pressurize to 0.03-0.05MPa, and maintain a total gas space velocity of 500-1000h. -1 The reaction is completed after 40-60 minutes, yielding a pretreated solution. Step S2: Add the pretreatment liquid to the multi-stage thermal decomposition reaction module, raise the temperature step by step at a rate of 3-5℃ / min, treat 300-500L / h of waste liquid, perform three-stage condensation and recovery, and treat for 3-4 hours. After treatment, pyrolysis liquid and non-condensable oxygen-enriched gas are obtained respectively. Step S3: Add the pyrolysis solution to the three-stage reaction tank, with a cathode potential of -0.15-0.25V and a cathode current density of 10-30A / m. 2 With an electrode spacing of 30-50mm and a rotation speed of 60-80rpm, non-condensable oxygen-enriched gas is introduced, with an aeration intensity of 0.1-0.3vvm and a treatment time of 40-60min / batch. After treatment, the temperature is controlled to 93-97℃ by PID, the rotation speed is 80-100rpm, and the reaction is kept at the temperature for 70-90min. The hydrogen peroxide concentration is adjusted to 1-2g / L to obtain a mixed solution. Step S4: Add the mixture to the diaphragm electrolytic cell, heat the cathode chamber to 90-95℃, heat the anode chamber to 85-90℃, set the electrode spacing to 30-40mm, and the cathode current density to 100-200A / m. 2 With a voltage of 2.5-3.5V, 100-200g / L sulfuric acid is added to the anode chamber, and an asymmetric square wave pulsed current is applied at a current density of 200-400A / m. 2 The on-time was 30-50ms, the off-time was 10-30ms, the frequency was 30-50Hz, and the deposition time was 6-8h, yielding deposited copper, oxygen, and hydrogen.
2. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The mixed gas in step S1 includes hydrogen, nitrogen and non-condensable oxygen-enriched gas. The non-condensable oxygen-enriched gas comes from step S2 in the continuous production process. The hydrogen comes from the hydrogen evolved in the cathode chamber in step S4 in the continuous production process. The volume concentration of the hydrogen is ≤4%.
3. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The preparation steps of the catalyst in step S1 are as follows: Step A1: Add spherical activated carbon to deionized water, heat to 90-100℃, wash for 30-40 min, remove and drain, add 5wt% nitric acid solution, heat to 50-60℃, treat for 4-5 h, after treatment is complete, wash with deionized water, adjust pH to 6.8-7.2, dry, then place in a muffle furnace, purge with nitrogen, heat to 340-360℃, calcine for 3-4 h, after calcine is complete, cool to 20-30℃ to obtain the pretreated carrier; Step A2: Add chloroplatinic acid and palladium chloride to deionized water, stir at 100-200 rpm for 15-25 minutes, add isopropanol as dispersant, stir for 8-12 minutes, and after stirring is complete, the impregnation solution is obtained. Step A3: Add the pretreated support to the impregnation flask, reduce the pressure to -0.08 to -0.09 MPa, degas for 30-40 min, add the impregnation solution, impregnate for 2-3 h, after impregnation is complete, restore to normal pressure, and rotary evaporate to obtain the catalyst precursor; Step A4: Under a hydrogen and nitrogen atmosphere, add the catalyst precursor into a tube furnace, heat to 260-300℃ at a heating rate of 3-5℃ / min, and carry out the reduction reaction for 4-6 hours. After the reaction is complete, cool down to 20-30℃ and purge with nitrogen for 30-40 minutes to obtain the catalyst.
4. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 3, wherein the mass ratio of chloroplatinic acid, palladium chloride, dispersant, and deionized water in step A2 is 0.052-0.056:0.015-0.019:0.054-0.058:1; The mass ratio of the pretreated carrier to the impregnation solution in step A3 is 1:0.5-0.9; In step A4, the volume ratio of hydrogen to nitrogen is 0.15-0.2:
1.
5. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The multi-stage thermal cracking reaction module mentioned in step S2 includes a preheating tank, a primary cracking tank, a secondary reaction stirring tank, and a tertiary reaction tank; The stepwise heating in step S2 is as follows: preheating tank temperature 40-60℃, first-stage reaction tank temperature 86-90℃, second-stage reaction stirring tank temperature 88-90℃, and third-stage reaction tank temperature 93-97℃.
6. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The three-stage condensation recovery in step S2 is as follows: the first stage cools down to 80-90℃, recovers the acidic condensate and returns it to the first-stage dewatering tank; the second stage cools down to 40-50℃, recovers the oxygen-containing condensate; and the third stage yields non-condensable oxygen-enriched gas.
7. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 6, characterized in that, A portion of the non-condensable oxygen-enriched gas is returned to step S1 to mix with hydrogen, while the other portion is introduced into the preheating tank and the bottom of the primary cracking tank for microbubble aeration, with an aeration intensity of 0.2-0.5 vvm.
8. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The three-stage reaction tank in step S3 is equipped with a liftable electrode assembly. The cathode of the liftable electrode assembly is made of stainless steel plate, and the anode is a titanium-based iridium-tantalum coated DSA anode.
9. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, In step S4, the diaphragm in the diaphragm electrolyzer is a perfluorosulfonic acid type cation exchange membrane with a thickness of 0.15-0.20 mm.
10. The method for recovering copper from PCB hydrogen peroxide micro-etching waste liquid by heating, decomposition, and electrolysis according to claim 1, characterized in that, The cathode chamber described in step S4 is equipped with an online hydrogen detector; The oxygen released from the anode chamber in step S4 is collected and dried by acid mist, and then combined with the third-stage non-condensable oxygen-enriched gas in step S2.